Reflection of postmodernism in Kurt Vonnegut’s selected fictions - Soofastaei, Elaheh; Jujar Singh, Hardev Kaur; Bahar, Ida Baizura; Mirenayat, Sayyed Ali (2016)
Kurt Vonnegut (1922-2007) is known as one of the best American postmodern writers in XX century. This paper attempts to look at three steps of postmodernism in three of his most popular novels, such as Player Piano, Cat’s Cradle, and Slaughterhouse-five. It will categorize the evolutionary process of postmodernism in these novels. The steps include accumulation, synthesis, and autonomy. Through Player Piano, accumulation copes with the separation between nature and culture in postmodernism. It investigates the presence of the objects made of nature and culture. Through Cat’s Cradle, synthesis will show the center of the evolution. And finally through Vonnegut’s magnum opus Slaughterhouse-five, autonomy will touch on his achievement as an autonomous entity.